Stem Cell Biology in Health and Disease - Dittmar, Thomas; Zänker, Kurt S. (Springer Netherlands : Imprint: Springer, 2010)
Stem Cell Biology in Health and Disease presents an up-to-date overview about the dual role of stem cells in health and disease. The Editors have drawn together an international team of experts providing chapters which, in this fully-illustrated volume, discuss: - the controversial debate on the great expectations concerning stem cell based regeneration therapies raised by the pluripotency of various stem cells. - the advantages and concerns about embryonic stem cells (ES cells), induced pluripotent stem cells (iPS cells) and adult stem cells, such as bone marrow-derived stem cells (BMDCs). - the type of stem cells, which has become of interest in the past decade, namely so-called cancer stem cells (CSCs). CSCs are now in the focus of cancer research since the eradication of tumour initiating cells would raise the changes of definitely cure cancer. Professor Dittmar and Professor Zänker have edited a must-read book for researchers and professionals working in the field of regenerative medicine and/or cancer.